Analysis of Risk Factors for External Genital Health of Women of Childbearing Age in Purwakarta Regency, Indonesia - Ruciah, Ruciah (HM Publisher, 2024)
Introduction: The health of women's external genitalia is an important aspect of reproductive health. This study aims to analyze the health risk factors for the external genitalia of women of childbearing age in Purwakarta Regency, Indonesia. Methods: This research is an analytical observational study with a cross-sectional design. The research sample was 240 women of childbearing age in Purwakarta Regency who were selected randomly. Data was collected through questionnaires and physical examination. Data analysis was carried out univariate and bivariate. Results: The results of the study showed that the risk factors for the health of the external genitalia of women of childbearing age in Purwakarta Regency were age, parity, and a history of sexually transmitted infections (STIs). Women aged more than 35 years have a higher risk of external genital health than women aged less than 35 years (OR = 2.65; 95% CI: 1.22-5.83). Women with parity more than 2 have a higher risk of external genital health than women with parity 1-2 (OR = 2.32; 95% CI: 1.14-4.71). Women with a history of STIs have a higher external genital health risk than women without a history of STIs (OR = 3.52; 95% CI: 1.58-8.17). Conclusion: Age, parity, and history of STIs are risk factors for external genital health in women of childbearing age in Purwakarta Regency.